Implementación y configuración de un servidor basado en linux para el laboratorio de desarrollo de software en la Universidad Técnica de Cotopaxi extensión La Maná en el periodo octubre 2014–febrero 2015 - Miranda Torres, Juan Carlos (2016)
This research work refers to the implementation and configuration of a server based in Linux for the Software Development Laboratory of Computer engineering and computing system career at the Cotopaxi Technical University, La Maná. With the constant evolution of the technologies in the last decades and the increment of information resources nowadays has generated the appearance of different types of servants that allow to maintain a control of all the resources in the net. The methodology, is guided in a qualitative and quantitative perspective; in this project was applied a study description field....